CAUSES AND PREVENTION OF CARDIOVASCULAR DISEASES AMONG YOUTH (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Cardiovascular diseases (CVD) have traditionally been associated with older populations, but recent epidemiological trends indicate a concerning rise in incidence among young adults aged 18-39 years. This article explores the multifaceted causes of CVD in youth, including lifestyle factors such as poor diet, sedentary behavior, obesity, smoking, substance abuse, and chronic stress, as well as emerging risks like sleep disorders, vaping, and social determinants of health. Prevention strategies emphasize primordial and primary interventions, including policy-level changes for healthy environments, lifestyle modifications, early screening, and targeted education. Drawing from recent literature, this review synthesizes evidence on risk factor prevalence, awareness gaps, and effective interventions. Findings suggest that addressing behavioral risks in adolescence and young adulthood could reduce long-term CVD burden by up to 50-70%. The discussion highlights gender differences, transitional challenges from pediatric to adult care, and the role of technology in prevention. Results from analyzed studies show suboptimal awareness (e.g.,